Molecular typing of vancomycin-resistant Enterococcus faecium with an automated repetitive sequence-based PCR microbial typing system compared with pulsed-field gel electrophoresis and multilocus sequence typing. (May 2013) - Kardén-Lilja, Minna; Vuopio, Jaana; Koskela, Markku; Tissari, Päivi; Salmenlinna, Saara
Abstract Background: Pulsed-field gel electrophoresis (PFGE) is the main typing method used for the molecular typing of vancomycin-resistant Enterococcus faecium (VREfm). However, more rapid and unambiguous typing methods are needed. DiversiLab, a repetitive sequence-based PCR (rep-PCR), offers an alternative method for strain typing. Methods: Thirty-nine VREfm isolates with known epidemiological relationships were characterized by semi-automated rep-PCR (DiversiLab), PFGE, and multilocus sequence typing (MLST). Results: The DiversiLab results were analysed in 2 ways: first relying solely on the DiversiLab software, and second by DiversiLab analysis combined with manual interpretation. The analysis with interpretation yielded more DiversiLab profiles, correlated better with PFGE and MLST, and grouped the isolates better according to their relatedness in time and space. However, most of the DiversiLab groups also included isolates with different PFGE and MLST types. Conclusions: DiversiLab provides rapid information when investigating a potential hospital outbreak. However, the interpretation of E. faecium DiversiLab results cannot be fully automated and is not always straightforward. Other typing methods may be necessary to confirm the analysis.